2000
DOI: 10.1007/bf03218117
|View full text |Cite
|
Sign up to set email alerts
|

Primary lymphoma of bone originating in a rib

Abstract: Malignant lymphoma originating in the bone is rare and is now recognized as being an independent clinicopathologic entity known as primary lymphoma of bone. A 60-year-old man complaining of right chest and back pain consulted our hospital for further examination. Chest X-ray and computed tomogram revealed osteolysis and a surrounding soft tissue mass in the sixth right rib. An ultrasonically-guided needle biopsy of the tumor was performed, and histologic examination indicated the dense proliferation of similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Malignant lymphoma originating in the bone is rare and can be seen as a lytic bone lesion with or without cortical invasion or extension into the contiguous soft tissues. Thus, this malignancy can invade the extrapleural fat (66). Treatment of lymphoma depends on the histologic subtype determined after biopsy.…”
Section: Neoplasmsmentioning
confidence: 99%
“…Malignant lymphoma originating in the bone is rare and can be seen as a lytic bone lesion with or without cortical invasion or extension into the contiguous soft tissues. Thus, this malignancy can invade the extrapleural fat (66). Treatment of lymphoma depends on the histologic subtype determined after biopsy.…”
Section: Neoplasmsmentioning
confidence: 99%
“…Review of literature corresponding to our 15‐year study period (2000‐2015) revealed 20 reports based either on cases series or isolated cases (Table ) in which 26 histologically confirmed chest wall lymphoma cases were described . Location of the swellings was the anterior chest wall/manubrium in 14 cases, left chest wall (four cases), right chest wall (three cases), lateral chest wall (NOS in two cases), back in one case and rib/chest wall swellings and NOS in two cases.…”
Section: Discussionmentioning
confidence: 99%
“…Primary lymphoma of the bone (PLB), which was first reported by Oberling, 12 now is recognized as an independent clinicophathologic entity. 4,13 PLB accounts for approximately 4.7% of extranodal lymphomas. 14 The majority of cases occur in long bones, pelvis, or spine, and rib involvement is rare (2% to 15% of cases of PLB).…”
Section: Discussionmentioning
confidence: 99%
“…14 The majority of cases occur in long bones, pelvis, or spine, and rib involvement is rare (2% to 15% of cases of PLB). 4,13 The mean age at presentation for PLB, according to a review by Ostrowski and associates, 15 was 46 years with male predominance. The most frequent symptoms are pain, swelling, and B symptoms (fever, night sweats, and body weight loss), as in other lymphoma conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation